Acid Orange II degradation through a heterogeneous Fenton-like reaction using Fe–TiO2 nanotube arrays as a photocatalyst. Issue 16 (28th April 2015) - Su, Yufeng; Wu, Zhi; Wu, Yongneng; Yu, Jiangdong; Sun, Lan; Lin, Changjian
<x xml:space="preserve">Abstract</x> A heterogeneous Fenton-like process using an Fe–TiO2 NTA photocatalyst in the presence of H2O2 was investigated and an obvious synergistic effect was achieved.